2013
DOI: 10.4067/s0718-09342013000300006
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of responsibility by Spanish and English speakers: How native language affects our social judgments

Abstract: The relationship between language and thought has received a great deal of attention in linguistics. An increasing amount of empirical literature now suggests that our native language can affect how we think about the world around us. The present study asked two groups of participants to read the same story and to judge the attribution of the responsibility of a character in the story who may have caused an accident. One group of participants consisted of native Spanish speakers reading a Spanish version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…On the other hand, bilingual Spanish speakers may be most successful in describing the actions and recognizing the appropriate level of blame to place on agents in purposeful versus accidental events. (This latter point, incorporating blame perception, falls in accordance with research by Tillman, Langston, and Louwerse (2013), which revealed differential blame placement according to language background and agentive language use.) If Spanish speakers preferentially encode actions, as demonstrated by the present research, they may also remember more information about severity and intent of said actions.…”
Section: Language Affects Word Type Recallsupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, bilingual Spanish speakers may be most successful in describing the actions and recognizing the appropriate level of blame to place on agents in purposeful versus accidental events. (This latter point, incorporating blame perception, falls in accordance with research by Tillman, Langston, and Louwerse (2013), which revealed differential blame placement according to language background and agentive language use.) If Spanish speakers preferentially encode actions, as demonstrated by the present research, they may also remember more information about severity and intent of said actions.…”
Section: Language Affects Word Type Recallsupporting
confidence: 87%
“…In contrast to English's use of agentive language, Spanish describes accidental events by conjugating the verb to match the affected object and stating the blamed party, if any, as an indirect object ("the chair was broken by him," or simply "the chair was broken"), creating a non-agentive syntax (Cunningham, Vaid, & Chen 2011;Tillman, Langston, & Louwerse 2013). The Spanish phrasing is typically created using the clitic "se," which allows speakers to use the middle voice when referencing the event, thereby removing any sense of blame from the person causing the accident (Quesada 1998).…”
Section: Agentive Language As a Source Of Difference Between Linguist...mentioning
confidence: 99%
See 1 more Smart Citation